2015
DOI: 10.1007/s10482-015-0519-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endophytic yeast diversity in rice leaves by a culture-independent approach

Abstract: Endophytic microorganisms inhabit internal plant tissues in the host plant without causing any symptoms or negative effects. Although the diversity of endophytes has been evaluated by both culture-dependent and culture-independent methods, less information is available on yeast communities. Therefore, in this study a culture-independent method was used to examine endophytic yeasts associated with rice leaves based on the large subunit of ribosomal DNA using a semi-nested PCR technique. Sequence analysis indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 63 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Chadha et al (2015) suggested that plant endophytic fungi can protect plants against various pathogen and pests and help plants survive under harsh biological or abiotic stresses. Tantirungkij et al (2015) reported that rice leaves harbor several new yeast strains. Khan et al (2015) isolated two fungal strains, Fusarium tricinctum RSF-4L and Alternaria alternata RSF-6L, which promote the growth of the host by phytohormone secretion.…”
Section: S Rrmentioning
confidence: 99%
“…Chadha et al (2015) suggested that plant endophytic fungi can protect plants against various pathogen and pests and help plants survive under harsh biological or abiotic stresses. Tantirungkij et al (2015) reported that rice leaves harbor several new yeast strains. Khan et al (2015) isolated two fungal strains, Fusarium tricinctum RSF-4L and Alternaria alternata RSF-6L, which promote the growth of the host by phytohormone secretion.…”
Section: S Rrmentioning
confidence: 99%
“…We found that Vishniacozyma globispora, a basidiomycete yeast, was more abundant in early planting sorghum leaves. Vishniacozyma species have been identified as rice endophytes, Arctic plant endophytes, and tropical forest tree endophytes (Tantirungkij et al 2015, Santiago et al 2017, Felix et al 2020. Another close relative is a psychrotolerant yeast isolated from a glacier (Tsuji et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The genus includes close to 20 identified species and many additional unclassified taxa, but only V . victoriae was previously reported as an endophyte, in Antarctic angiosperms Deschampsia antarctica and Colobanthus quitensis (Santiago et al ., 2017), and in rice leaves (Tantirungkij et al ., 2015). Vishniacozyma victoriae was highly prevalent in our data set, however we also found high occurrence of V. carnescens (former Torulopsis carnescens ), and several additional Vishniacozyma species that were present at lower levels.…”
Section: Discussionmentioning
confidence: 99%